A distribuição de subvenções sociais e o clientelismo na Assembléia Legislativa do Estado de Minas Gerais - Dias, Wladimir Rodrigues (2006)
This paper deals with the incidence of clientelism in the Brazilian legislative system, by means of a case study on the social subsidies distributed by representatives working in the Minas Gerais State House of Representatives in the 90s. At that time, each state representative had at their disposal a certain amount of resources to apportion, following his own criteria and directing it to whomever they discerned, provided some legal limits were observed. In the study, theories on the clientelism issue were utilized and assumed in me condition of a cultural element that permeates social and political relations in Brazil. Also used by this study were the analytical background emanated by the new institutional theoretical vein that made itself present through public choice theories, notably in its contribution to legislative studies of a distributivist matrix, and the historical new mstitutionalism, from which the concept of path dependency was adopted, as well as other correlated theories. The theory of games was also utilized for the construction of a simple model depicting the influence that the apportioning of social subsidies had on the logic of legislature practices. The analysis of data concerning the distribution of subsidies, legislative production and electoral performance has allowed for the establishment of important conclusions about the role occupied by the distribution of patronage benefits, such as the legislature subsidies, in the political-legislative arena. Throughout that period, representatives presented a reduced number of legislative propositions aimed at common interests, whilst Governors tabulated elevated and stable figures regarding legislative performance. Once subsidies were extinct, it was noted that representatives started to legislate more often on subjects with social reach or of collective interest, that the Executive Branch bad difficulties performing in its legislative "fury", and that the lack of subsidies from the State House of Representatives, or of any analogous patronage means, represented a clear obstacle for the electoral performance of candidates. However, it was found that, even though it was interrupted in 1999, patronage found its ways back onto the political scene in 2003, by means of the creation of a new instrument, similar to its antecessor. The legacy left by the so-called rapture mat the House of Representatives underwent was me growth of the amount of legislative initiatives regarding matters of general interest.